42. RETROSPECTIVE PGT-A ANALYSIS FOR MULTIPLE DISPLACEMENT AMPLIFICATION (MDA) PRODUCTS OF EMBRYOS CORRESPONDING TO 21 SPONTANEOUS ABORTIONS BY NGS. (August 2019) - Shen, X.; Chen, D.; Fu, Y.; Ding, C.; Xu, Y.; Zhong, Y.; Xu, Y.; Zhou, C.
Abstract : Introduction: Preimplantation genetic testing for aneuploidy (PGT-A) is widely used to identify aneuploidy embryos, thereby reducing miscarriage rate and improving the clinical outcome of in vitro fertilization (IVF). But there are many reasons for miscarriage. Not all miscarriages are caused by embryonic aneuploidy. Moreover, PGT-A has its inherent defects, the results of PGT-A may not fully represent the true karyotype of embryos. Many problems still exist in this technology: 1. Biases caused by whole genome amplification (WGA) or high-throughput detection techniques; 2.Embryo mosaicism. Therefore, it remains unclear what percentage of spontaneous abortion can be prevented by PGT-A. Since 2015, our center has adopted multiple displacement amplification (MDA) as the first step in all PGT cycles. So a complete library of MDA products has been well-established. Material & methods: We collected PGT cycles performed for monogenic diseases (PGT-M) at our center from January 2015 to December 2017. Cycles in which the blastocyst biopsy and single blastocyst transplantation were applied, and spontaneous miscarriage appeared during early pregnancy, and MDA products of the embryos were frozen were considered eligible. Exclusion criteria: cycles in which PGT-A had been conducted and the embryo was already selected according to the PGT-A results. All MDA products were performed PGT-A using next generation sequencing (NGS) by Illumina NextSeq ® 550 platform. The software determined the ploidy status with 0.01X read coverage. Results: A total of 21 MDA products were detected, and 4 of them were unable to evaluate due to amplification failure or poor test data. The PGT-A results of the remaining 17 embryos showed that 47.1% (8/17) embryos were euploidy, 11.6% (2/17) embryos were segmental chromosomal aneuploidy (46, XN, -(1)(q23.3-q44)(85.03Mb) and 46, XN, +(13)(q11-q34)(95.75Mb)), 27.8% (5/18) of embryos were whole chromosomal aneuploidy mosaicism (the proportion of mosaicism range from 21 to 47%) and 2 cases were trisomy (trisomy 21 and trisomy 22). 6 patients performed karyotype analysis of abortion tissues, among which PGT-A results of 4 cases (3 cases were normal, one was trisomy 22) were consistent with the karyotype of abortion tissues. However, 2 cases showed aneuploidy mosaicism (46, XN, +(mosaic)(19)(30%) and 46, XN, -(mosaic)(6)(44%)) by PGT-A, while the karyotype of their abortion tissues were normal. Conclusions: Our study showed that PGT-A could prevent a proportion of spontaneous abortion. However, embryos with low ratio of mosaicism may not be the cause of miscarriage. In fact, spontaneous abortion of these cases was caused by other factors. How high the proportion of mosaicism may lead to miscarriage still requires further research to confirm.